Fate of Warm Pacific Water in the Arctic Basin. Issue 20 (19th October 2021) - Lin, Peigen; Pickart, Robert S.; Våge, Kjetil; Li, Jianqiang
Abstract: Pacific Summer Water (PSW) plays a critical role in the ecosystem of the western Arctic Ocean, impacting sea‐ice melt and providing freshwater to the basin. Most of the water exits the Chukchi Sea shelf through Barrow Canyon, but the manner in which this occurs and the ultimate fate of the water remain uncertain. Using an extensive collection of historical hydrographic and velocity data, we demonstrate how the PSW outflow depends on different wind conditions, dictating whether the warm water progresses eastward or westward away from the canyon. The current carrying the water westward along the continental slope splits into different branches, influenced by the strength and extent of the Beaufort Gyre, while the eastward penetration of PSW along the shelfbreak is limited. Our results provide the first broad‐scale view of how PSW is transferred from the shelf to the basin, highlighting the role of winds, boundary currents, and eddy exchange. Plain Language Summary: Warm Pacific water that flows northward through Bering Strait significantly influences the melting of sea‐ice, the distribution of freshwater, and the ecosystem of the Arctic Ocean. North of Bering Strait, the water progresses poleward across the shallow Chukchi Sea shelf, with most of it draining from the shelf through Barrow Canyon. Presently, the manner in which the flow exits the canyon, as well as its ultimate fate in the basin, remains unclear. We analyzed historical data sets of temperature, salinity, and velocity, and found that the local wind alters the manner in which the water exits Barrow Canyon to the east and west, as well as the corresponding distribution of Pacific Summer Water. The current carrying the water westward along the continental slope subsequently splits into different branches farther downstream. This is modulated by the strength and extent of the Beaufort Gyre, a large recirculating flow in the basin. In contrast, the signature of the warm water in the current flowing to the east is limited. Here, we provide the first observational broad‐scale view of the pathways and evolution of warm Pacific‐origin water from the shelf to the basin, and clarify the effects of wind, boundary currents, and small‐scale turbulent motions. Key Points: Outflow of Pacific Summer Water (PSW) through Barrow Canyon is dictated predominantly by the local wind The westward flow carrying the water away from the canyon bifurcates downstream, modulated by the strength and extent of the Beaufort Gyre The eastward flow emanating from the canyon progresses far downstream, but the signature of the PSW is limited